Oral health of an indigenous population in northeastern Brazil: a cross-sectional Study of the Fulni-ô ethnic group - Koike, Bruna Del Vechio; Valões, Rosangela Maria Pereira; Cazal, Claudia; Pereira, Vanessa Cardoso; Fraga, Carlos Alberto de Carvalho; Carmo, Rodrigo Feliciano do; Pereira, Meireane Firmino; Guimarães, Manoel Pereira; Souza, Carlos Dornels Freire de; Armstrong, Anderson da Costa (São Paulo Medical Journal, 2025)
BACKGROUND: There is a lack of studies evaluating the oral health of traditional indigenous communities in Brazil. OBJECTIVES: Thus, the objective of this study was to describe the oral health characteristics of the indigenous Fulni-ô ethnic group in Northeast Brazil. DESIGN AND SETTING: A cross-sectional observational investigation was conducted within the Project on Atherosclerosis among Indigenous Populations. METHODS: This study included participants of both sexes from the Fulni-ô ethnic group. The participants included in this investigation underwent a comprehensive oral health evaluation by a registered and experienced dentist to assess oral health and identify potentially malignant oral lesions. Participants with suspicious lesions were referred for biopsy. Shapiro-Wilk, Mann-Whitney, and Student’s t-tests were used, and measures of central tendency and dispersion were described. Statistical significance was 5%. RESULTS: A total of 104 individuals were included in this study. The prevalence of the use of tobacco derivatives was 94.0%, with similarities between sexes. The prevalence of oral changes in this study population was 84.4%. Fifty-one individuals who underwent oral reassessment were referred for oral lesion biopsy. CONCLUSIONS: This study demonstrated a high prevalence of oral alterations in the Fulni-ô population. Histopathological analyses indicated the presence of mild oral epithelial dysplasia in five cases.